Makrozoobenthos As A Bioindicator Of Water Quality In The Masang Kecil River In West Pasaman Regency - Gusna Merina; Jabang Nurdin; Ahmad Mursyid; Wandanil Putra; Reffi Aryzegovina; Rezi Junialdi (Journal of Multidisciplinary Science, 2022)
Sungai Masang Kecil is located in the middle of the PT Andalas Agro Industri (PT AAI) palm oil plantation and mill. This activity will have an impact on aquatic biota, especially benthos. Benthos occupies an important position in the food chain and lives permanently on the substrate to be used as a bioindicator of pollution. This study aimed to determine the Community Structure of Macrozoobenthos and the indicator species of water pollution in the Masang Kecil River around the PT AAI area, West Pasaman Regency. This research was conducted using a purposive sampling method with three sampling points, namely upstream and two downstream points after the Wastewater Treatment Plant (IPAL) and after the confluence of tributaries. Sampling using Surber net size 30 x 30 cm. The results of identifying the types of Bento's organisms as a whole identified as many as 45 species. Most species are found in Class Insecta. Based on the diversity index, the water quality in PT AAI's river basin was classified as unpolluted, and it could be concluded that the benthic condition was in good condition on a scale of 4. In the current study, the Diptera order as an indicator of polluted water was most commonly found among orders from other insect classes, namely, ten species. However, there were nine species from the Order Ephemeroptera as an indicator of clean waters and six species for Trichoptera.